Avaliação da atividade antioxidante do ácido fítico de germe de milho Corn germ phytic acid antioxidant activity evaluation - Cristina Tostes Filgueiras (Química Nova, 2009)
The obtained corn germ phytic acid (CGPA) antioxidant potential was evaluated through the deoxyribose, bathophenanthroline (BPS) and DPPH• assays. In the concentration of 130.5 μM of CGPA the hydroxyl radical maximum sequestering antioxidant activity was 29.3% while standard phytic acid (SPA) presented this maximum activity of 18.2% in the concentration of 33.2 μM of SPA. The BPS assays revealed that the chelation activity towards Fe2+ increased concurrently with the increase of CGPA concentration and its Fe2+ contact time. Finally, DPPH• assay showed that CGPA and SPA did not present electron-donating capacity to DPPH•.